Lingga Village Government's Efforts to Accelerate Reducing Stunting Rates - Dwi Nur Handayani; Pardi, Pardi; Sujendra, Bima; Mutmainnah; Anny Riwayati (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Failure to thrive is experienced by a child whose height does not match his age, often called stunting. Stunting is a health problem that will impact the future of a nation because one of the benchmarks of a country that is said to be developed is that the country has a healthy and bright generation. Currently, Indonesia is faced with the problem of the high prevalence of stunting toddlers from 2021 by 24.4% to 2022 to 21.6%, which has only decreased by 2.8%. The decrease has not reached the target of 14% in 2024. This study aims to describe and analyze the efforts of the Lingga Village government to accelerate stunting reduction using qualitative research methods. The research showed that the Lingga Village government's efforts to reduce stunting were through socialization, growth monitoring, development monitoring, sanitation, and clean water.